2019
DOI: 10.1177/1751143719870095
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity troponin measurement in critical care: Flattering to deceive or ‘never means nothing’?

Abstract: Introduction Troponin elevation is central to the diagnosis of acute type 1 myocardial infarction. It is, however, elevated in a range of other conditions, including type 2 myocardial infarction, and this setting is increasingly associated with adverse clinical outcomes. Patients within intensive care frequently have at least one organ failure together with a range of co-morbidities. Interpretation of troponin assay results in this population is challenging. This clinical uncertainty is compounded by the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Thus, whilst many early reports in patients with COVID-19 equated a troponin rise with myocardial infarction, typically this is more like to be related to sepsis and associated systemic inflammatory response, pro-coagulant status, and myocarditis. Without regular screening with cardiac biomarkers, in the absence of major ECG changes, myocardial injury in patients with COVID-19 can be frequently missed and yet is associated with an increased mortality [62,63]. Likewise, stroke can be very challenging to recognise in patients who are intubated and ventilated, due to masking of clinical signs and symptoms with sedation and neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whilst many early reports in patients with COVID-19 equated a troponin rise with myocardial infarction, typically this is more like to be related to sepsis and associated systemic inflammatory response, pro-coagulant status, and myocarditis. Without regular screening with cardiac biomarkers, in the absence of major ECG changes, myocardial injury in patients with COVID-19 can be frequently missed and yet is associated with an increased mortality [62,63]. Likewise, stroke can be very challenging to recognise in patients who are intubated and ventilated, due to masking of clinical signs and symptoms with sedation and neuromuscular blockade.…”
Section: Discussionmentioning
confidence: 99%
“… [68] However, troponin elevation is frequently observed in critically ill patients regardless of reasons for admission. Furthermore, assays for troponin have become increasingly sensitive, [70] and the association between troponin and hospital mortality is substantially attenuated after controlling for confounding factors. [71] The causes of troponin elevation are likely multifactorial, and increases are associated with myocardial membrane leakage and/or cytokine apoptosis, but not macrothrombi.…”
Section: Diagnosismentioning
confidence: 99%
“…The CHARIOT-ED substudy increased illness severity has been demonstrated to be closely associated with cTn elevation, not only in ED, but also in the context of sepsis and patients admitted to intensive care. [23][24][25][26][27] The most important observation of this study is that increasing cs-cTnI concentrations (regardless of the manufacturer's 99th percentile value) are associated with increasing 30-day mortality. Furthermore, the AUCs of 0.863 and 0.859 suggest that cs-cTnI testing on admission, outside of the context of acute T1MI, could provide useful prognostic information for clinicians about the patients newly presented to them.…”
Section: Discussionmentioning
confidence: 72%